2001
DOI: 10.1001/archpsyc.58.11.1025
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Bipolar Disorder to Chromosome 18q and the Validity of Bipolar II Disorder

Abstract: Affected sibling pairs with BPII discriminated between families who showed evidence of linkage to 18q, and families who did not. Families with a BPII sibling pair produced an increased lod score and improved linkage resolution. These findings, limited by the small number of BPII-BPII sibling pairs, strengthen the evidence of genetic linkage between BPAD and chromosome 18q, and provide preliminary support for BPII as a genetically valid subtype of BPAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 31 publications
9
58
0
1
Order By: Relevance
“…An analysis in a subset of these pedigrees indicates that siblings with BPII disorder contribute a significant portion of the increased allelic sharing. 36 Several other studies of bipolar disorder have implicated 18q, 15,37-39 but as might be expected with a complex disorder, 40 not all studies have replicated this finding. 38,[41][42][43] The next strongest finding in the present study was at D4S1629 on 4q32 (NPL ¼ 2.8, Po0.004) using the BPUP affection model, which coincides with a region identified by Ekholm et al 44 Ekholm et al 44 studied 41 Finnish pedigrees and reported a Z max of 3.3 at D4S1629.…”
Section: Discussionmentioning
confidence: 95%
“…An analysis in a subset of these pedigrees indicates that siblings with BPII disorder contribute a significant portion of the increased allelic sharing. 36 Several other studies of bipolar disorder have implicated 18q, 15,37-39 but as might be expected with a complex disorder, 40 not all studies have replicated this finding. 38,[41][42][43] The next strongest finding in the present study was at D4S1629 on 4q32 (NPL ¼ 2.8, Po0.004) using the BPUP affection model, which coincides with a region identified by Ekholm et al 44 Ekholm et al 44 studied 41 Finnish pedigrees and reported a Z max of 3.3 at D4S1629.…”
Section: Discussionmentioning
confidence: 95%
“…The familial nature of hypomania has raised questions whether BDII is a distinct category. 33,35 Congruent with this view are the findings of McMahon et al 36 showing that families with BDII cases had the strongest evidence of linkage to chromosome 18q21-23 markers.…”
Section: Diagnosis Of Bdmentioning
confidence: 95%
“…found evidence linking psychotic symptoms in bipolar patients with 13q31 and 22q12 but not 10p12-14 or 18p11.2, all regions where bipolar and schizophrenia susceptibility overlap. The region 18q21-23 appears associated particularly with milder bipolar disorder, suggesting perhaps that bipolar II forms a valid subtype (McMahon et al 2001). Faraone et al (2004) have tentatively identified three new chromosomal regions associated with age of onset in bipolar disorder.…”
Section: The Role Of Genetic Factorsmentioning
confidence: 99%